Drosophila chitinous aECM and its cellular interactions during tracheal development. Issue 3 (28th October 2015) - Öztürk‐Çolak, Arzu; Moussian, Bernard; Araújo, Sofia J.
Abstract : The morphology of organs, and hence their proper physiology, relies to a considerable extent on the extracellular matrix (ECM) secreted by their cells. The ECM is a structure contributed to and commonly shared by many cells in an organism that plays an active role in morphogenesis. Increasing evidence indicates that the ECM not only provides a passive contribution to organ shape but also impinges on cell behaviour and genetic programmes. The ECM is emerging as a direct modulator of many aspects of cell biology, rather than as a mere physical network that supports cells. Here, we review how the apical chitinous ECM is generated in Drosophila trachea and how cells participate in the formation of this supracellular structure. We discuss recent findings on the molecular and cellular events that lead to the formation of this apical ECM (aECM) and how it is influenced and affects tracheal cell biology. Developmental Dynamics 245:259–267, 2016 . © 2015 Wiley Periodicals, Inc. Key Findings: Cell‐ECM interactions. Drosophila apical ECM. Formation of taenidial ridges and their interaction with the underlying cells.